2016
DOI: 10.1016/j.cell.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Modulates T Cell Metabolism and Enhances Survival and Anti-tumor Activity

Abstract: SummaryMetabolic activity is intimately linked to T cell fate and function. Using high-resolution mass spectrometry, we generated dynamic metabolome and proteome profiles of human primary naive T cells following activation. We discovered critical changes in the arginine metabolism that led to a drop in intracellular L-arginine concentration. Elevating L-arginine levels induced global metabolic changes including a shift from glycolysis to oxidative phosphorylation in activated T cells and promoted the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,056
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,196 publications
(1,169 citation statements)
references
References 76 publications
26
1,056
4
2
Order By: Relevance
“…15 Tcells activation consumes large amount of L-arginine, and the underlying mechanism was nicely demonstrated. 15 Given the fact that arginase-mediated L-arginine depletion profoundly suppress T-cell immune response, 20,21 L-arginine supplementation is a good idea to feed the T-cells, and to inhibit tumor growth. However, malignancies, especially solid tumors, can escape from or impair immune attack by multiple mechanisms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…15 Tcells activation consumes large amount of L-arginine, and the underlying mechanism was nicely demonstrated. 15 Given the fact that arginase-mediated L-arginine depletion profoundly suppress T-cell immune response, 20,21 L-arginine supplementation is a good idea to feed the T-cells, and to inhibit tumor growth. However, malignancies, especially solid tumors, can escape from or impair immune attack by multiple mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“…13,14 Thus, following these theories, L-arginine supplementation was recently proved to enhance T-cell survival and antitumor activity. 15,16 In this study, we tried to validate our hypothesis that L-arginine supplementation and PD-1/PD-L1 pathway blockade can facilitate spontaneous immune response against osteosarcoma. We established immunocompetent mouse models using BALB/ c mice bearing in situ osteosarcoma or metastasized osteosarcoma, and then treated them with L-arginine and/or a-PD-L1 antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the tight connection existing between mitochondrial metabolism and the shape of the mitochondrial network (see [209] for a review), we could expect an involvement of mitochondrial dynamics in TILs metabolism inside the tumor mass. Of note, it is still unknown whether or not differentiation to an exhausted phenotype in TILs could also affect mitochondrial dynamics, in addition to its well-established role on T EX mitochondrial metabolism [207,210]. Recently, by a microarray analysis in chronic viral-infected patients fit has been found that exhausted CD8+ T cells show significant downregulation in the expression of several genes associated with mitochondrial OXPHOS metabolism, and upregulation of the oxidative stress pathway.…”
Section: Cell Exhaustionmentioning
confidence: 99%
“…Повышенная метаболическая ак-тивность в ходе экспансии ex vivo может приводить Т-клетки к состоянию, в котором они имеют низкую способность к персистенции in vivo и, следовательно, к слабому противоопухолевому ответу. Результаты не-давнего исследования показали, что добавление арги-нина в культуральную среду в ходе экспансии ex vivo способно усилить окислительный и подавить гликоли-тический метаболизм, что позволяет добиться получе-ния большого количества более эффективных проти-воопухолевых клеток [52]. Таким образом, условия культивирования, в которых метаболическая активность противоопухолевых Т-клеток ограничивается в ходе экспансии ex vivo, могут приводить к продукции клеток с характеристиками, способствующими их использова-нию в иммунотерапии.…”
Section: т-клетки Cd8unclassified